Ceramic nanomaterials and nanotechnology III proceedings of the 106th Annual Meeting of The American Ceramic Society, Indianapolis, Indiana, USA (2004) (Ceramic transactions, 2005)
This volume contains papers on the synthesis and processing of inorgainc nanomaterials and nanocomposites; structure-property correlations at the nanoscale; understanding of fundamental phenomena in nanoscale systems and processes; applications of nanostructured materials; and industrial development of nanomaterials.